Beyond the Sacrificial Fantasy: Body, Law, and Desire - Guanzini, Isabella (Open theology, 2024)
From its origins, the Christian religious imaginary has been inhabited by the sacrificial fantasy, which finds its most radical symbol in the crucified body. According to the principle of imitatio Jesu , believers have always been called to consider pain as an experience to be lived and shared with Christ, to be offered to him as a gift of self to the Other. Already the masters of suspicion condemned this ascetic-religious cult of sacrifice and showed its dehumanizing and superegoic side, characterized by the violence of abuse, authoritarianism, submission, and above all the denial of life. However, this beneficial and liberating critique has removed the donative and not merely alienating aspect not of the sacrificial body, but of the symbolic sacrifice. Starting from a close dialogue between systematic theology and (Lacanian) psychoanalysis, this contribution aims to question both the sacrificial (religious) fantasy in its alienating character and the equally superegoic drive of the imperative of unlimited enjoyment as a reaction to any kind of symbolic limitation. Against this background, an attempt will be made to think of a form of sacrifice that follows the logic of the gift (of the body), without being subjected to a logic of alienating exchange.